KINERJA PEGAWAI DAN TENAGA KONTRAK PADA BIDANG PENUNJANG NON MEDIK RUMAH SAKIT UMUM ANUTAPURA PALU - Maryanti, Tri; Riadi, Slamet; Baji, Haslinda (Katalogis, 2021)
The field of non-medical support is one of the fields of health care support at Anutapura general hospital which oversees several installations or service units including Installation of Hospital Facilities and Infrastructure Maintenance (IPSRS), Nutrition Installation, Central Suply Sterilization Department (CSSD) Installation, Sanitation Installation, Laundry Installation. The focus of this research is on laundry installations. The purpose of this thesis research is to find out how the performance of employees and contract workers in carrying out their duties. To find out the performance of employees and contract workers in this thesis research using the theory of Robbins, (2006:260) with performance indicators including the quality of work, quantity of work, timeliness of work, effectiveness, independence and work commitment. Using descriptive research methods with a qualitative approach. The source of the data is obtained through primary data which is the result of interviews with several heads of rooms and supporting attendees at anutapura hammer general hospital. The results of the performance research are based on the quality of work, there are still some jobs that cannot always be carried out, the quantity of work that the entire work volume can be completed properly, the timeliness of the work of the employee still needs to be repaired, coming in on time or more often late while the timeliness of contract labor according to work time, work effectiveness that almost all contract workers can use machines and laundry facilities while employees are still there who cannot use it, independence in carrying out work can do the work it is responsible for, while work commitments that there are still employees and contract workers work commitment needs to be improved.